From Tidore to the Cape of Good Hope: Identity Transformation, Diasporic Agency, and Cultural Legacy of Tuan Guru Imam Abdullah bin Qadi Abdussalam - Yanuardi Syukur (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
This article examines the life and legacy of Tuan Guru Imam Abdullah bin Qadi Abdussalam, a noble ulama from the Sultanate of Tidore exiled by the VOC to South Africa in the 18th century, from a historical anthropology perspective. Born in Tidore (1712) and died in Cape Town (1807), he represents the complexity of encounters between local identity, colonial politics, and Islamic knowledge transmission across continents. Using Ortner’s “serious games” framework and Kottak’s concept of enculturation, this article identifies three dimensions of Tuan Guru’s contribution. First, as a diasporic subject, he transformed from Tidore prince to religious authority in exile. His childhood enculturation in Tidore shaped his learning capacity, later reproduced in South Africa. Second, as an agent of knowledge transmission, he demonstrated two faces of agency: agency-as-power through symbolic resistance to colonialism, and agency-as-projects through reproducing Nusantara Islamic tradition—writing six Qur’anic manuscripts from memory, the theological work Ma’rifat al-Islam wa al-Iman, and establishing the first madrasah and mosque in Cape Town. Third, as cultural legacy, he became a symbol of struggle honored across generations—from Nelson Mandela’s pilgrimage to his grave to contemporary discourse on proposing him as an Indonesian National Hero. This article argues that Tuan Guru actively played his own “serious games” under colonial pressure, building Islamic institutions foundational for Cape Town’s Muslim community today. This research contributes to understanding Nusantara diaspora dynamics and identity negotiation at the intersection of locality, colonialism, and globalization.